The Importance of Parents Role in Familiarizing Chilfren with Fasting from an Early Age - Ahmad Nur Huda (Journal Markcount Finance, 2024)
Fasting is a mandatory worship that must be carried out in the month of Ramadan, but this is not for children who have not reached the age of puberty. Children's worship is the responsibility of every parent, whether or not children are able to carry out worship is a big task for parents in educating children. This study aims to determine the role of parents in the habit of fasting Ramadan in children. This research is a qualitative research through interviews and analyzed descriptively. This research was conducted on 4 parents who had children aged 5-8 years in Babakan Gadog Village, Kujangjaya Village. Results. of this study indicate that, the role of parents in the process of fasting habituation in early childhood is carried out by supervising, guiding and giving examples to children, by fasting children will be more healthy, increase worship and patience in children. The game environment affects children in fasting, so that in the process of getting used to fasting, parents must supervise children while playing so they are not influenced by friends who do not observe fasting.